Applying the Restitution Triangle Strategy to Address Student Discipline Issues in Elementary Schools - Alif Maulana Permadi; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
Student discipline issues remain a persistent challenge across educational levels, often disrupting the learning environment and student development. This study aims to investigate the application of the restitution triangle as an alternative strategy for addressing disciplinary problems among elementary school students. Developed by Diane Gossen, the restitution triangle offers a restorative framework consisting of three main stages: stabilizing identity, validating misbehavior, and seeking underlying beliefs. A descriptive qualitative method was employed, with data collected through observations, interviews, and documentation involving students and teachers at Gunungsimping 02 State Elementary School. The findings reveal that the implementation of the restitution triangle effectively reduced the frequency of disciplinary violations, enhanced students' self-awareness, and strengthened teacher-student relationships. These results suggest that the restitution triangle is a promising strategy for fostering a positive school culture grounded in self-discipline and personal responsibility.